THE EFFECT OF STEM LEARNING MODEL (SCIENCE, TECHNOLOGY, ENGINEERING, AND MATH) ON THE CRITICAL THINKING SKILLS OF SCIENCE AND TECHNOLOGY STUDENTS IN CLASS IV SDN CIPONDOH 4 TANGERANG CITY - Mawardi, Mawardi; Perdiansyah, Ferry; Ushaybiah, Zahwa Muflihah (PIONIR: JURNAL PENDIDIKAN, 2024)
The purpose of the study was the effect of STEM learning model on critical thinking skills of fourth grade students of SDN Cipondoh 4 Tangerang City. This research was conducted at SDN Cipondoh 4 Tangerang City, 2023/2024 school year consisting of two classes, namely class IV A totaling 24 people as the experimental class and class IV B totaling 24 people as the control class with a total of 48 students. This study uses an experimental method with a form of Quasi Experimental design type Nonequivalent Control Group Design with data collection techniques used, namely interviews, observations, documentation and tests. Data analysis techniques in this study include descriptive analysis of data, analysis requirements test (normality and homogeneity test), hypothesis testing to determine the effect of science critical thinking skills of fourth grade students using the STEM learning model. The results of the pre-test and post-test showed that the average value of control class students was 71.16, and the average of experimental class students was 93.25, so the increase was 22.09. The experimental class post-test results showed a t-value of 3.233, a t-table value of 1.677 with a significance level value of 0.002> 0.05. These results indicate that there is an influence on students' critical thinking skills between students who use the STEM (Science, Technology, Engineering, Mathematics) learning model and students who use conventional learning models. This study concludes that there is an effect of using the STEM learning model on the critical thinking skills of science fourth grade students of SDN Cipondoh 4 Tangerang City.Keywords: Critical thinking skills, Science learning, STEM